2007
DOI: 10.1073/pnas.0702137104
|View full text |Cite
|
Sign up to set email alerts
|

Real-time control of the energy landscape by force directs the folding of RNA molecules

Abstract: The rugged folding-energy landscapes of RNAs often display many competing minima. How do RNAs discriminate among competing conformations in their search for the native state? By using optical tweezers, we show that the folding-energy landscape can be manipulated to control the fate of an RNA: individual RNA molecules can be induced into either native or misfolding pathways by modulating the relaxation rate of applied force and even be redirected during the folding process to switch from misfolding to native fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
86
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 38 publications
4
86
0
Order By: Relevance
“…Single molecule force experiments have far exceeded simple proof-of-principle experiments and have been used to elucidate the folding thermodynamics and kinetics for several RNAs [101][102][103][104][105][106]. This approach has answered one of the most fundamental questions in nucleic acid structure formation, providing direct evidence for the long-held nucleation model for duplex involving formation of 2-3 base pairs prior to rapid formation of the remainder of the duplex [107].…”
Section: Rna: Present and Futurementioning
confidence: 99%
“…Single molecule force experiments have far exceeded simple proof-of-principle experiments and have been used to elucidate the folding thermodynamics and kinetics for several RNAs [101][102][103][104][105][106]. This approach has answered one of the most fundamental questions in nucleic acid structure formation, providing direct evidence for the long-held nucleation model for duplex involving formation of 2-3 base pairs prior to rapid formation of the remainder of the duplex [107].…”
Section: Rna: Present and Futurementioning
confidence: 99%
“…Though, hysteresis has been observed in single molecule experiments [24][25][26][27][28][29][30][31], however, many aspects of these phenomena are yet to be explored. In a recent work [32], Kapri showed that using the work theorem [33], it is possible to extract the equilibrium force-extension curve from the hysteresis loops.…”
Section: Introductionmentioning
confidence: 99%
“…In part, the difficulty arises because complex proteins generally fold slowly and tend to aggregate in bulk experiments (8), a problem that can be avoided in mechanical unfolding of single proteins. Indeed, single-molecule mechanical methods have recently provided new possibilities for directly probing the energy landscapes of proteins and RNA because they can monitor the population of partially folded states (9)(10)(11)(12)(13)(14)(15)(16). In addition, these experiments can explore regions of the energy landscape that are inaccessible in conventional experiments, thus providing a complete picture of the folding process (17)(18)(19)(20).…”
mentioning
confidence: 99%